Pengaruh Kebiasaan Membaca terhadap Kemampuan Menulis Siswa - Ririn Sabriadi (Institut Nalanda, 2025)
This research aims to determine the influence of reading habits on students' writing abilities at Hasanuddin Aviation Vocational School, Makassar. This research uses quantitative methods with a correlational approach. Data was collected through questionnaires about reading habits and writing tests. The results of the analysis show that there is a significant positive influence between reading habits and students' writing abilities. Therefore, it is recommended that students involve themselves more often in reading activities to improve their writing skills.